Basis for fortifying wheat flour with micronutrients in Peru - Sanabria, Hernán (2007)
Current government policies bring about new perspectives for improvements in the nutritional aspect. However, since mid 2005, the Peruvian government has implemented a wheat flour fortification program with micronutrients. Act # 28314 approved a modification to the mandatory fortification of wheat flour with iron, increasing the amount of iron from 30 mg/kg of wheat flour to 55 mg of ferrous sulphate, in addition to 1-2 mg/kg folic acid, among other micronutrients. This article reviews aspects related to iron and folic acid, as well as information on iron and folic acid defficiencies, such as anemia and neural tube defects. Finally, recommendations are provided based on the information presented to promote the use of food fortified with wheat flour.